(untitled) (Journal Of Educational and Psychological Researches, 2022)
The aim of the research is to know the level of mental motivation among students of the Arabic language departments in the Faculties of Education in the universities of Baghdad Governorate and its relationship to their attitudes towards the profession, and the level of orientation towards the profession among students of the Arabic language departments in the Faculties of Education. And the correlational relationship between mental motivation and career orientation among students of Arabic language departments in the Faculties of Education, and the current research is determined by students of Arabic language departments in the Faculties of Education and the universities (Education Ibn Rushd- University of Baghdad, Education- Al-Mustansiriya University, Iraqi University- Education)for the academic year (2019-2020). The researcher selected a sample consisting of (100) male and female students from the fourth stage in the Arabic language departments, after which she adopted the mental motivation scale (Al-Rabei, 2011) and built the career-orientation scale, and after applying the two tools, she concluded that the level of the research sample was high in mental motivation as well as In the direction towards the profession, and that the relationship between mental motivation and the orientation towards the profession was a high positive relationship. The researcher drew some conclusions and recommended a number of subsequent recommendations and proposals.